A bibliometric analysis of African dental research and the sustainable development goals, 2016–2023 - El Tantawi, Maha; Bhayat, Ahmed; Foláyan, Moréniké Oluwátóyìn (Frontiers in Oral Health, 2024)
BackgroundThe successful implementation of the 2030 sustainable development Agenda in Africa requires active participation from all sectors, including the dental research sector. The aim of this study was to review dental research published by authors affiliated with institutions in African countries from 2016 to 2023, to map papers related to the sustainable development goals (SDGs), and to identify areas of emphasis and gaps in SDGs-related papers on oral health in Africa.MethodsWe conducted a bibliometric analysis of dental literature in Africa (2016–2023) using Scival for performance analysis and VOSviewer for science mapping. The papers addressing and not addressing the SDGs were compared regarding impact, authorship metrics and key phrases. We identified the topic clusters with the greatest number of papers. The key phrase co-occurrence networks and the authors and countries collaboration networks were mapped.ResultsThere were 4,173 papers and 622 (14.9%) addressed the SDGs, especially SDG3. SDGs papers had greater impact and were more likely to be published in open access journals than non-SDGs papers. Egypt, Nigeria and South Africa had the greatest number of papers and citations. Four of the top ten authors were females. Most of the top ten journals were open access and only three were in quartile 1 (Q1) journals. Springer and Elsevier were the top publishers. The top research clusters addressed rehabilitative care including implants, endodontics, ceramics and zirconia. SDGs papers, however, addressed oral hygiene in caries prevention and to control systemic diseases. Collaboration networks were affected by geographic location and languages. Dental research in Africa is concentrated in three countries and mainly addresses rehabilitative care. SDGs papers had an impact above the global average and addressed prevention and non-communicable diseases.ConclusionsThere is minimal yet increasing contribution of African countries to the evidence on oral health and the SDGs. The focus is on a limited number of SDGs, and publications are from very few countries in Africa. There is a need to focus oral health-related SDGs research on addressing local problems.